Assessing the Nature of Risk Management Implementation in Manufacturing Small Medium Enterprises in Nigeria - Igbokwe Nkemakonam; Mba Wilfred (Archives of Current Research International, 2019)
The survival of manufacturing small and medium enterprises depends on its capability to anticipate and prepare for setbacks, challenges and risks, rather than waiting for it to happen. Thus the purpose of this study was to investigate the nature of risk management implementation in manufacturing small and medium enterprises in Nigeria. A survey methodology was applied during this investigation. And the results revealed that as the owner/manager entrepreneurial experience grows, risk management experience is gained. Thereby leading to a better risk perception, where a more sophisticated risk management approach is implemented that ensures its survival during political or economic crises.